Analyzing Wimbledon - Klaassen, Franc; Magnus, Jan R. (ITF Coaching & Sport Science Review, 2013)
This paper highlights some of the topics discussed in our recently published book ‘Analyzing Wimbledon’, which provides a statistical analysis of many topics relevant for tennis players, coaches, commentators, and spectators.